A alfabetização das crianças das classes populares na escola pública: uma proposta de formação continuada de professores (as) - Todero, Marissandra (2017)
This study presents the results of a dissertation for the stricto sensu postgraduate course as one of the requirements to obtain the Professional Master’s Degree in Education at Universidade Federal da Fronteira Sul, under the teme "Literacy in public school". We sought different authors, from the Popular Education field to theoretically support and guide this work. The case study was carried out at a state school, located in the city of Erechim - RS, and our initial intention was to understand how the continuing teacher education can contribute to the literacy of children from the popular classes in the public school to help their emancipation as subjects. Our motivations came from the academic and professional life, which has always been focused on the Educational Research, from the perspective of Popular Education, as well as from our experiences based on the reality of the popular classes. In this study, we point out some features of literacy and public school, as well as Popular Education and continuing teacher education. Our thoughts and refletions came from a challenging context and we sought to achive our initial intention aim. We can highlight that during this research we found out the urges for continuing education that enables literacy teachers to have a theoretical thought on the literacy process of the children from the popular classes and their pedagogical practices, which are carried out in this context of the public school. After considering the principles of Popular Education and the perspective of the emancipation of the subjects, we made up this intervention proposal, which is based on specific study meetings with the literacy teachers.